1997
DOI: 10.1172/jci119130
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of desmoglein-3 specific T cells from patients with pemphigus vulgaris.

Abstract: Pemphigus vulgaris (PV) is a cutaneous autoimmune disease characterized by blister formation in the suprabasilar layers of skin and mucosae and anti-desmoglein-3 (Dsg3) autoantibodies bound to the surface of lesional keratinocytes and circulating in the serum of patients. This disease can be reproduced in neonatal mice by passive transfer of patients' IgG, indicating that humoral immunity plays an important role in the pathogenesis of PV. Currently, the role of T lymphocytes in the development of PV is not cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
126
2
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(154 citation statements)
references
References 51 publications
19
126
2
6
Order By: Relevance
“…We found that only APC expressing HLA-DRB1*0402 and HLA-DQB1*0503 were capable of presenting Dsg3 to autoreactive Th1 and Th2 clones and that their proliferative response was blocked by anti-DR and anti-DQ Ab, respectively. Therefore, HLA-DRB1*0402 and HLA-DQB1*0503 appear to be the major HLA class II alleles involved in restriction of T cell responses against Dsg3 peptides, thus confirming previous evidence of DRB1*0402 as a restriction element for the presentation of Dsg3-derived peptides (11,12,23).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We found that only APC expressing HLA-DRB1*0402 and HLA-DQB1*0503 were capable of presenting Dsg3 to autoreactive Th1 and Th2 clones and that their proliferative response was blocked by anti-DR and anti-DQ Ab, respectively. Therefore, HLA-DRB1*0402 and HLA-DQB1*0503 appear to be the major HLA class II alleles involved in restriction of T cell responses against Dsg3 peptides, thus confirming previous evidence of DRB1*0402 as a restriction element for the presentation of Dsg3-derived peptides (11,12,23).…”
Section: Discussionsupporting
confidence: 86%
“…This observation clearly demonstrates that both autoreactive Th1 and Th2 cells are present in PV, although at different frequencies during the course of the disease. These findings extend previous studies that derived both Dsg-reactive Th1 and Th2 clones from the peripheral blood of patients with PV (11)(12)(13)(14)23). Their detection, however, requires assay systems of adequate sensitivity, as demonstrated herein compared with ELISPOT analysis (16).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…An independent study by Lin et al (20) identified T cell responses from PV patients to three polypeptides (aa 145-192, aa 240 -303, and aa 570 -614) representing stretches of the ECD1-5 of Dsg3. Noteworthy, polypeptide aa 240 -303 contains a peptide DG3(250-266) which was identified in the present study and by Wucherpfennig and coworkers (19).…”
Section: Discussionmentioning
confidence: 99%
“…13 Além do conceito bem definido sobre o papel da imunidade humoral por meio da patogenicidade dos anticorpos da subclasse IgG4 contra a Dsg1, foi demonstrado que os linfócitos T de pacientes com FS mostram respostas proliferativas quando expostos ao ectodomímio da Dsg1 recombinante produzida pelo sistema de expressão do baculovírus, comprovando o envolvimento da imunidade celular no processo. 14,15 Quanto às possíveis etiologias, é importante o fator genético, havendo forte associação entre FS e quatro HLA DRB1 específicos, que são DRB1 0404, 1402, 1406 e 1404. 16 Simulídeos têm sido implicados como agentes que poderiam precipitar o FS em pessoas imunogeneticamente suscetíveis.…”
Section: Patogeniaunclassified